2021
DOI: 10.31603/ae.6116
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Emissions Analysis of BE85-Gasoline Blends on Spark Ignition Engine

Abstract: This study aims to reveal the performance and exhaust emissions of a spark ignition (SI) engine fueled by a gasoline-bioethanol mixture. The main performance characteristics of the SI engine tested are torque, power output; thermal efficiency, brake specific fuel consumption, and brake mean effective pressure. Meanwhile, the exhaust emissions seen are carbon monoxide and hydrocarbons. The test is carried out by comparing the performance of the SI engine under standard conditions without modification with gasol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…The increase in industrial activity and the increasing world population cause fuel consumption to increase so that it interferes with air quality and causes an energy crisis [1], [2]- [4]. This makes the need for environmentally friendly alternative fuels very crucial [3], [5].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in industrial activity and the increasing world population cause fuel consumption to increase so that it interferes with air quality and causes an energy crisis [1], [2]- [4]. This makes the need for environmentally friendly alternative fuels very crucial [3], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hal positif lain yang dapat dihasilkan adalah terciptanya unit-unit usaha mikro yang dapat menambah berpotensi pendapatan masyarakat. Optimisme dari kami terhadap keberhasilan kegiatan ini sangatlah besar, di mana penelitian tentang beberapa jenis bahan bakar alternatif telah berhasil dilakukan dan dipublikasikan pada jurnal internasional bereputasi (Nanlohy et al, 2018(Nanlohy et al, , 2022Nanlohy & Riupassa, 2020). Selain itu pada penelitian awal dalam skala laboratorium telah berhasil dilakukan dan dipublikasikan pada sebuah konferensi internasional di Malaysia pada bulan April 2022.…”
Section: Pendahuluanunclassified
“…In addition, a recent studies on the effect of a mixture of ethanol and isooctane on laminar burning characteristics [ 17 19 ], octane reaction on the methyl tert -butyl ether (MTBE) with gasoline [ 20 ]. Furthermore, application research on the effect of the use of ethanol and isooctane against flame speed [ 21 ], dynamic spray [ 22 ], macroscopic spray characteristics under flash boiling conditions [ 23 , 24 ], NOx emissions [ 25 , 26 ], particulate matter [ 27 ], and their impact on fuel efficiency have also been applied to the SI engine, and the results show that there is a significant performance improvement [ [28] , [29] , [30] ].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous research was carried out about bioethanol by modifying the ignition degree with a usual standard on the spark ignition engine [ 31 , 32 ]. These studies stated that the burning rate increased for all variaous blended of the bioethanol–isooctane; moreover, especially for BE30, they also found that NOx was measurably reduced [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%